К воросу о представлении крымских татар к званию Героя Советского Союза. Новые архивные свидетельства - Куртсеитов, Р.Д. (Культура народов Причерноморья, 2013)
В статье продолжен анализ участия крымских татар во Второй мировой войне, героизм,
проявленный солдатами и офицерами на полях сражений. На основе архивных материалов
рассматриваются новые факты представления крымских татар к званию Герой Советского Союза,
причины замены высшей награды СССР другими наградами. Дается статистика награждений
военнослужащих призванных военными комиссариатами Крымской АССР. У статті продовжено аналіз участі кримських татар у Другій світовій війні, героїзм
проявлений солдатами і офіцерами на полях битви. На основі архівних матеріалів розглядаються нові
факти подання кримських татар до звання Герой Радянського Союзу, причини заміни вищої нагороди
СРСР іншими нагородами. Дається статистика нагороджень військовослужбовців покликаних
військовими комісаріатами Кримської АРСР. The article deals with the continuation of the analysis of participation and heroism of the Crimean
Tatar soldiers and officers of in the Second World War. On the basis of archival material of the generalized data
bank (GDB) ‘Memorial’ of the Central Archive of the Ministry of Defense of the Russian Federation and other
military archives of the Second World War newly found facts related to the nomination of Crimean Tatars to the
title of Hero of the Soviet Union are considered. This article analyzes the reasons for changing the highest
award of the Soviet Union by other awards. Statistics of military personnel awarding of different nationalities
called up from the Crimean ASSR is given. There was a significant discrepancy of replacing the highest military
award by other prizes. Out of 24 nominations of the Crimean Tatars to the title of the Hero, only 6 were
nominated during and immediately after the war, while representatives of other nationalities were denied in 13
cases. The ratio of called Crimean Tatars to the front was 15% to 85% of other nationalities. We studied the
"Prize papers" of awarding 7010 officers, 10 184 sergeants and 7,571 of enlisted personnel that were called up
by military commissariats of the Crimean Autonomous Soviet Socialist Republic.
All four representatives nominated to the title of the Hero twice called up from the Crimean Autonomous Soviet
Socialist Republic were Crimean Tatars, only one of them Sultan Amet-Khan was nominated twice, whereas
Anatoly Abilov and Jaffer Osman Topchy were never nominated to this title during the war. Moreover, the
second (postmortal) nomination to the title of Hero of Osman Jaffer Topchy was awarded the Order "Great
Patriotic War" of the first degree. Our research findings prove the existence of "ethnic factor" during awarding
the representatives of the deported people.